PROVERBS AS A PAREMIOLOGICAL UNIT (Scientific journal of the Fergana State University, 2024)
This article examines the fact that proverbs are widely studied in linguistics as a linguocultural unit and clearly express the cultural image and national identity of each nation in the system of linguistic images. Using examples of proverbs with the child component analyzed the fact, that children's characteristics in proverbs are expressed in consonance with the values of the Uzbek people.